The crisis of secularism in India - Needham, Anuradha Dingwaney; Sunder Rajan, Rajeswari (Duke Univ. Press, 2007)
Secularism's historical background -- Secularism and democracy -- Sites of secularism : education, media, and cinema -- Secularism and personal law -- Conversion